2009
DOI: 10.2503/hrj.8.101
|View full text |Cite
|
Sign up to set email alerts
|

Methods of Evaluating Texture in Japanese Radishes and Changes in Texture during a Light-pickling Process

Abstract: For efficient research into breeding, cultivation, storage and marketing of vegetables, objective methods of quality evaluation are needed. Texture (Firmness) is the most important factor in evaluating the quality of Japanese radish (Raphanus sativus L.) root. We proposed a firmness evaluating method of fresh and lightly-pickled radish roots using a Texture Analyzer in the following way. Disks (10 mm in diameter and 5 mm thick) were obtained from the defined positions of radish roots of various cultivars and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…The results suggested that the changes in hardness had a significant correlation with the changes in pectin, especially for protopectin. The results obtained also showed a good agreement with previously reported findings, which presented a high correlation between hardness and the amount and type of pectin (Hudson & Buescher, ; Komiyama et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…The results suggested that the changes in hardness had a significant correlation with the changes in pectin, especially for protopectin. The results obtained also showed a good agreement with previously reported findings, which presented a high correlation between hardness and the amount and type of pectin (Hudson & Buescher, ; Komiyama et al ., ).…”
Section: Resultsmentioning
confidence: 97%